Effects of Increased Soil Scarification Intensity on Natural Regeneration of Scots Pine Pinus sylvestris L. and Birch Betula spp. L. - Mona Saursaunet; Karen Marie Mathisen; Christina Skarpe (Forests, 2018)
Achieving an optimal density of trees is essential for the final yield in commercial forestry. Soil scarification is commonly used in Scandinavia in order to produce successful regenerations of Scots pine (Pinus sylvestris L.), especially in areas with risk of browsing damage by moose (Alces alces L.). The research presented in this paper provides knowledge on how increased intensity of soil scarification affects the regeneration of pine and birch (Betula spp. L.). A total of 67 stands were treated with different intensities of soil scarification. Tree seedling density and current annual growth (CAG) were measured one to five years after scarification. Results showed that the density of pine and birch seedlings increased with soil scarification intensity. CAG of pine decreased with scarification intensity. CAG of downy birch decreased with proportion of exposed mineral soil, but increased with proportion of exposed humus. The effect of soil scarification intensity on CAG of both tree species was relatively weak. Results suggest that although increased scarification intensity had a positive effect on seedling establishment, the effect on early growth may be unfavourable. Further research is needed in order to evaluate the long-term effects of soil scarification intensity on growth.